Respuesta :

We have to find the value of the expression [tex]i^{233}[/tex]

We know that the below values.

[tex]i^2=-1\\i^4=1[/tex]

Hence, in order to find the value of the given expression, we can first rewrite it in terms of [tex]i^4[/tex]

[tex]i^{233}=(i^4)^{58}\cdot i[/tex]

Now, we know that [tex]i^4=1[/tex]

Hence, we have

[tex]i^{233}=(1)^{58}\cdot i[/tex]

[tex]i^{233}=1\cdot i[/tex]

[tex]i^{233}=i[/tex]

C is the correct option.

The value of [tex]i ^{233}[/tex] is [tex]i[/tex].

Given to us

  • [tex]i ^{233}[/tex]

What is the value of  [tex]i ^{233}[/tex]?

We know the value of iota(i ) is equal to √-1.

therefore, the expression can be written as,

[tex]i^{233} = (\sqrt{-1})^{233}[/tex]

It can be furthered written as,

[tex]i^{233} = (\sqrt{-1})^{233}\\\\[/tex],

Using the exponential rule [tex]x^a \times x^b = x^{(a+b)}[/tex]

[tex]i^{233} = (\sqrt{-1})^{232} \times (\sqrt{-1})\\\\[/tex]

Using [tex](x^a)^b =x^{ab}[/tex],

[tex]i^{233} = [(\sqrt{-1})^2]^{116} \times (\sqrt{-1})\\\\i^{233} = (-1})^{116} \times (\sqrt{-1})\\\\i^{233} = 1 \times (\sqrt{-1})\\\\i^{233} = 1 \times i\\i^{233} = i[/tex]

Hence, the value of [tex]i ^{233}[/tex] is [tex]i[/tex].

Learn more about the Exponential rule:

https://brainly.com/question/17286040